The Digital Transformation of the Automotive Industry Catalysts, Roadmap, Practice - Winkelhake, Uwe.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Building on his decades of experience as a consultant and project manager in the automotive industry, the author develops comprehensive and pragmatic recommendations for action regarding the digital transformation of the automotive and supplier industries. At the heart is the transition from a vehicle-focused to a mobility-oriented business model. Based on the catalysts of the digital change, four digitizsation fields are structured, and a roadmap for their transformation is presented. The topics of comprehensive change in corporate culture and an agile and efficient information technology are covered in detail as vital success factors. Selected practical examples of innovative digitizsation projects provide additional ideas and impulses. An outlook on the automotive industry in the year 2040 completes the discourse.
Preface -- Introduction -- Information technology as driver of digitisation -- "Digital lifestyle" - Future employees and customers -- Technologies for digitization solutions -- Vision Digitised Automotive Industry 2030 -- Roadmap for sustainable digitisation -- Corporate culture and organisation -- Information technology as an enabler of digitisation -- Examples of innovative digitisation projects -- Car Mobility 2040.
Keywords: Automotive engineering; Database management; Industrial Management; Business information services; Industries; Automotive Engineering; Database Management System; Industrial Management; IT in Business; Industries; Automobiles -- Design and construction -- Technological innovations; Automobile industry and trade -- Technological innovations; Automobiles -- Electronic equipment; Automobiles -- Automatic control